2022
DOI: 10.51847/nsmkjxudzr
|View full text |Cite
|
Sign up to set email alerts
|

Objective Criteria in Evaluating the Consequences of The Posttraumatic Scars

Abstract: Most of the population has scars which are related to a traumatic event. In current forensic practice, two-dimensional measurement of the scar surface is used to analyze a scar, but for an objective evaluation of the scars, it would be necessary to measure its volume to capture all the characteristics. Moral suffering as a negative consequence of the presence of the scar should also be measured by using psychometric scales to attest the degree of internalization or production of aesthetic damage given that any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…There were no significant differences in adverse events between the two treatments, with both PRP and HA injections being generally well-tolerated by patients. This suggests that both treatments are safe options for managing the symptoms of advanced knee arthritis until knee-replacement procedures and their consequences become unavoidable [ 31 ]. Further research involving larger sample sizes, extended follow-up periods, and diverse patient populations is necessary to confirm these findings and yield more comprehensive insights into the comparative efficacy of PRP and HA injections in the management of advanced KOA.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in adverse events between the two treatments, with both PRP and HA injections being generally well-tolerated by patients. This suggests that both treatments are safe options for managing the symptoms of advanced knee arthritis until knee-replacement procedures and their consequences become unavoidable [ 31 ]. Further research involving larger sample sizes, extended follow-up periods, and diverse patient populations is necessary to confirm these findings and yield more comprehensive insights into the comparative efficacy of PRP and HA injections in the management of advanced KOA.…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation, patients' attention to scars is evaluated after receiving treatment, while there are few reports on the psychological evaluation of patients 36,52 . In this regard, the scale Mekeres, GM et al reported to assess the psychological condition of burn scar patients could be used for reference 53 . Although improvement in scars is associated with improvement in depression, the extent to which scar therapy improves depression has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…36,52 In this regard, the scale Mekeres, GM et al reported to assess the psychological condition of burn scar patients could be used for reference. 53 Although improvement in scars is associated with improvement in depression, the extent to which scar therapy improves depression has not been reported. Therefore, in addition to the treatment of scars, whether other treatments are needed to improve patients' psychopsychological disorders is worth discussing.…”
Section: Hotspots Analysismentioning
confidence: 99%